MOTIVASI LATIHAN TIM BOLAVOLI PUTRA SMA OLAHRAGA MASMUR SELAMA MASA PANDEMI - M. Arif Rifaldi; Ramadi Ramadi; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The goal to be achieved through this research is to find out the training motivation of the Masmur Sports High School men's volleyball team during the pandemic. This type of research is descriptive which aims to reveal how "Motivation for the men's volleyball team at Masmur Sports High School during a pandemic". The variables in this study were the motivation of male volleyball players at Masmur Sports High School during the pandemic as the independent variable and playing volleyball as the dependent variable. The location of this research was at the Masmur Sports High School volleyball court during the pandemic. The time of this research is planned for August 2022-February 2022. The results of a thorough data analysis on the training motivation of the Masmur Sports High School men's volleyball team show that: (1) the answers "strongly agree" with a frequency of 317 or 52.83% and an achievement score of 1485; (2) the answer "agree" with a frequency of 498 or 8% and an achievement score of 230; (3) "doubtful" answers with a frequency of 16 or 2.67% and an achievement score of 80; (4) the answer "disagree" with a frequency score of 33 or 5.5% achievement score of 115; (5) the answer "strongly disagree" with a frequency of 186 or 31% achievement score 930. Thus an achievement score of 2639 is obtained, while the most expected highest score (ideal score) is 3000. By comparing the achievement score (2639) to the ideal score ( 3000) obtained a percentage score of 88%. If the percentage of the achievement score (88%) is compromised by table 2 as a comparison criterion, it is concluded that the training motivation of the men's volleyball team at Masmur Sports High School is in the good category. Overall, the achievement level of motivation for the men's volleyball team at Masmur Sports High School was obtained from 20 respondents with 30 questions of 88%. Sudjana (1996:355) that the classification level of achievement between 80% -89% is in the good classification. This means that the training motivation for the Men's Volleyball Team at Masmur Sports High School is in the good classification. Keywords: Motivation, Men's Volleyball Team Training, Masmur Sports High School, during a pandemic